Expatriates at the base-of-the-pyramid. Precarious employment or fortune in a foreign land? - Holtbrügge, Dirk (Journal of Global Mobility, 2021)
Purpose International human resource management research has only recently started to recognize the many millions of people who engage with the international labor market as low-skilled self-initiated expatriates. In contrast to company-assigned expatriates, they predominantly come from less-developed countries (often from rural areas) and independently decide to pursue an international career. The aim of this study is apply an expatriate-centered perspective and explore how expatriates at the base of the pyramid perceive the conditions of their international employment. Design/methodology/approach The paper is based on a qualitative study among self-initiated expatriates in the tourism and hospitality industry in the United Arab Emirates (UAE). Findings Two theoretical categories that reflect the evaluation of expatriate employment were identified, namely the social comparison with friends and family who stayed at home as well as with other expatriates and locals and the temporal comparison to the situation before the expatriation and the prospective situation after the expatriation. Both categories largely differ from the concepts and categories prevalent in the expatriate literature. Research limitations/implications The study contributes to the understanding of the temporal and transitory dimensions of expatriation, which have been barely addressed in the academic literature. It shows that self-initiated expatriation often represents a break in the professional and personal biography. It is less perceived as linear continuation of a steadily advancing career path than a restart or springboard to the future. The results are situated in the tourism and hospitality sector in the UAE and cannot be generalized to other countries and industries. Practical implications The study emphasizes the relevance of social inclusion, equal opportunities, a safe work environment and a relaxed corporate culture for expatriates at the base of the pyramid. Originality/value While research about self-initiated expatriates usually compares them with company-backed assignees, this comparison is not salient in the narratives of the interviewees in this study. Instead, low-skilled self-initiated expatriates predominately compare their current foreign assignment with the situation in their home country. This social comparison reflects their perceived reality of life better than a fictional comparison with highly skilled and company-assigned expatriates that is prevalent in the academic expatriation literature. By emphasizing an expatriate-centered perspective, the study supports and extends Piore's (1979) application of segmented labor market theory.
Keywords: Self-initiated expatriates; Labor migration; Expatriation motives; Social comparison; Temporal comparison; United Arab Emirates; Chancengleichheit